COVID-19 and sporting activity (Australian Institute of Sport, 2020)
The Australian Institute of Sport, partnering with the Australian Olympic Committee and Paralympics Australia in the lead-up to the Tokyo Olympic and Paralympic Games, is committed to providing the National High Performance Sports System with timely, evidence-based information on the Coronavirus (COVID-19) that recognises the unique concerns and context associated with high performance sport.